Reason and Time in the French Baroque: François Couperin’s “Leçons de ténèbres pour le mercredi saint” (1714) - Karacsony, N.; Rucsanda, D.M. (Universitatea Transilvania Brasov, 2023)
The present paper aims to investigate the manner in which the structure of a certain musical discourse can suggest the superiority of reason above senses, as well as the static or flowing quality of time. In this sense, François Couperin’s (1668-1733) Leçons de ténèbres pour le mercredi saint (1714) was analyzed, striving to observe the manner in which the composer approaches certain parameters of the musical discourse (rhythm and metre, tempo, dynamics, ornaments) in order to suggest the meaning of the sacred text and to induce the listener a certain feeling of withdrawal, the absorption of the senses that can eventually lead to the mystical union with the Divine, accomplished through reason. The paper strives to highlight the differences between the Italian and French Baroque, as reflected in the work of Couperin, who strove to accomplish in his compositions the union between the French and Italian styles and forms. The question that arises is whether music is capable to express the passive state of devotion and contemplation, despite its unfolding in time, and whether it is possible to conceive the musical discourse in a manner that refrains from the anticipation of its future evolutions.
Keywords: François Couperin; French Baroque; time; rhythm; stillness